Types and Functions of If-conditionals in Lecture Introductions - Ting, Su Hie; Yeo, Jiin-Yih (Taiwan International ESP Journal, 2021)
This study examined the types and functions of if-conditionals in lecture introductions. The data comprise 144 if-conditionals from a 37,373-word corpus (3.85 per 1000 words). A majority of if-conditionals are direct conditionals (89.6%), with 10.4% of indirect conditionals. Of the direct conditionals, 72.9% are expressed as open condition and 16.7% as hypothetical condition. Hypothetical if-conditionals are mainly for hedging about the students’ knowledge, and less frequently for hedging about the lecturer’s own knowledge, hedging the intended interpretation of the utterance, expressing politeness, or making indirect requests. Most of the if-conditional clauses are in an initial position (88.9%), with some in medial (1.4%) and end (9.7%) positions. Initial if-conditional clauses mainly serve as a framework for subsequent propositions by presenting assumptions, but are minimally used for contrasting, exemplification, and exploring options. Medial if-conditional clauses function as a qualifier. End if-conditional clauses are used to remind students of a prior statement. The study shows that if-conditionals have an important information-linking function, and the functions of ifconditionals are linked to the positioning of if-clauses